Czego nie wiemy o Hannie Szumańskiej-Wertheimowej? Wydawnictwo (in spe) „Wisła” 1943–1944 - Mitzner, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The aim of this paper is to try and outline the activities of Hanna Szumańska-Wertheim in Warsaw during the 1943–1944 period. It provides information about the arrest of her husband, Stanisław Wertheim, and about her underground cultural undertakings (the “Wisła” publishing house). The author also draws the readers’ attention to Szumańska-Wertheim’s activities as a courier in the resistance movement.